2021
DOI: 10.1016/j.msard.2020.102603
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity behavior in people with multiple sclerosis during the COVID-19 pandemic in Israel: Results of an online survey

Abstract: Physical activity behavior in people with multiple sclerosis during the COVID-19 pandemic in Israel: Results of an online survey, Multiple Sclerosis and Related Disorders (2020), doi:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 13 publications
3
29
0
Order By: Relevance
“…Studies show that patients with pre-existing NCDs have found it difficult to maintain a healthy lifestyle during the COVID-19 pandemic and associated lockdown measures introduced by countries 227 . Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…Studies show that patients with pre-existing NCDs have found it difficult to maintain a healthy lifestyle during the COVID-19 pandemic and associated lockdown measures introduced by countries 227 . Patients with coronary heart disease [228][229][230][231][232] , neurological disorders 233,234 , diabetes 235,236 and cancer 237,238 have had to compromise on their physical activity routine, dietary patterns, and social connectedness in particular 227,236,239,240 as did families with children who had chronic respiratory diseases 193,241 . Poor glycemic control in diabetics due to altered lifestyle was reported in many studies [242][243][244][245][246][247][248] , while one study in India reported an improvement in the glycemic status of patients with type II diabetes mellitus 249 .…”
Section: Lifestyle Factors In Patients With Pre-existing Ncdsmentioning
confidence: 99%
“…Some of these adverse consequences may also increase risk factors for more severe COVID-19 disease, such as vascular comorbidities and obesity ( Salter et al., 2021 , Louapre et al., 2020 ). Impact of reduced physical activity was also reported in the aforementioned Israeli study, with 32% reporting a notable reduction in fitness ( Kalron et al., 2021 ). Several guidelines for managing MS recommend the promotion of health behaviours such as exercise, diet, smoking cessation and stress or mood management including referral to allied health professionals to optimise health outcomes for people with MS.…”
Section: Discussionmentioning
confidence: 61%
“…However, most participants reported reduced physical activity because of the bushfires and COVID-19 pandemic (55% and 54% respectively). An Israeli study reported similar changes in physical activity behaviour due to the COVID-19 pandemic, with 51% of participants with MS reporting a decrease in leisure time physical activity, and 38% reporting an increase ( Kalron et al., 2021 ). Reduced physical activity is particularly problematic given a previous report that the majority of people with MS were not meeting physical activity recommendations ( Marck et al., 2020 ).…”
Section: Discussionmentioning
confidence: 86%
“…Noting that MS or disease-modifying therapies do not adversely affect the morbidity of COVID-19, the researchers focused on the possibility of sedentary behaviors. The authors stated that 33.3% of the patients had decreased physical activity ( Kalron et al., 2021 ). In our study, COVID-19 positive people with MS were compared with negative cases.…”
Section: Discussionmentioning
confidence: 99%